Validity and Reliability of a Commercial Force Sensor for the Measurement of Upper Body Strength in Sport Climbing - Berit K. Labott; Berit K. Labott; Steffen Held; Tim Wiedenmann; Ludwig Rappelt; Pamela Wicker; Lars Donath (Frontiers Media S.A., 2022)
Recreational and professional climbing is gaining popularity. Thus, valid and reliable infield strength monitoring and testing devices are required. This study aims at assessing the validity as well as within- and between-day reliability of two climbing-specific hanging positions for assessing the maximum force with a new force measurement device. Therefore, 25 experienced male (n = 16) and female (n = 9) climbers (age: 25.5 ± 4.2 years, height: 176.0 ± 9.9 cm, weight: 69.7 ± 14.5 kg, body composition: 11.8 ± 5.7% body fat, climbing level: 17.5 ± 3.9 International Rock Climbing Research Association scale) were randomly tested with climbing-specific hang board strength tests (one-handed rung pulling and one-handed bent arm lock-off at 90°). The Tindeq, a load cell-based sensor for assessing different force-related variables, was employed together with a force plate (Kistler Quattro Jump) during both conditions. Data analysis revealed excellent validity for assessment with Tindeq: The intra-class correlation coefficient (ICC) was 0.99 (both positions), while the standard error of the measurement (SEM), coefficient of variation (CV), and limits of agreement (LoA) showed low values. Within day reliability for the assessment with Tindeq was excellent: rung pulling showed an ICC of 0.90 and arm lock-off an ICC of 0.98; between-day reliability was excellent as well: rung pulling indicated an ICC of 0.95 and arm lock-off an ICC of 0.98. Other reliability indicators such as SEM, CV, and LoA were low. The Tindeq progressor can be applied for the cross-sectional and longitudinal climbing strength assessment as this device can detect training-induced changes reliably.